2006
DOI: 10.1086/508380
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods, Family, and Substance Use: Comparisons of the Relations across Racial and Ethnic Groups

Abstract: This study examines how substance use among adolescents is related to several risk and protective factors derived from two ecological contexts: the neighborhood and the family. It explicitly investigates how the relationships between substance use and the factors vary across different racial and ethnic groups. Findings suggest many common correlates and processes of substance use for adolescents, regardless of race or ethnicity, including that neighborhood safety is associated with substance use. There are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…Studies using objective characteristics have generated mixed results: disadvantaged and deteriorating neighborhoods have been positively associated with alcohol and marijuana initiation and use (Furr-Holden et al, 2011; Smart et al, 1994; Tucker et al, 2012), negatively associated (Snedker et al, 200), and unassociated (Allison et al, 1999; Fagan, Wright and Pinchevsky, 2013). Subjective neighborhood measures provide more consistent findings that accord with social disorganization theory; adolescents report greater initiation and substance use if they report feeling less safe in their neighborhoods (Burlew et al, 2009; Choi et al, 2006; Theall et al, 2009; Tucker et al, 2013). Because of these mixed findings, we examine both objective and subjective neighborhood characteristics as predictors of change and cessation in adolescent marijuana use.…”
Section: Introductionmentioning
confidence: 57%
“…Studies using objective characteristics have generated mixed results: disadvantaged and deteriorating neighborhoods have been positively associated with alcohol and marijuana initiation and use (Furr-Holden et al, 2011; Smart et al, 1994; Tucker et al, 2012), negatively associated (Snedker et al, 200), and unassociated (Allison et al, 1999; Fagan, Wright and Pinchevsky, 2013). Subjective neighborhood measures provide more consistent findings that accord with social disorganization theory; adolescents report greater initiation and substance use if they report feeling less safe in their neighborhoods (Burlew et al, 2009; Choi et al, 2006; Theall et al, 2009; Tucker et al, 2013). Because of these mixed findings, we examine both objective and subjective neighborhood characteristics as predictors of change and cessation in adolescent marijuana use.…”
Section: Introductionmentioning
confidence: 57%
“…However, in keeping with the strategy used in a variety of SDM studies (Choi, Harachi, & Catalano, 2006; Herrenkohl et al, 2003), conceptually plausible direct associations between the exogenous variables and dependent problem behavior variables were examined if justified empirically. Six exogenous variables were included in all of the hypothesized structural models: religious coping, spirituality, positive family life, single-mother household status, gender, and age.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, this study used 1990 Census data in the National Longitudinal Study of Adolescent Health, which is a mostly-white sample. Although many studies have reported significant associations with self-reported neighborhood quality and substance use, those studies typically report a composite measure of substance use, or combine delinquency outcomes with substance use (Byrnes et al, 2011; Burlew et al, 2009; Choi et al, 2006; Hadley-Ives et al, 2000; Lambert et al, 2004; Joon Jang and Johnson, 2001). It is important to examine substances separately instead of a composite measure because of potentially different mechanisms by which neighborhood quality may influence ATOD use.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies have examined effect modification by race/ethnicity (Browning, 2012; Choi et al, 2006; Fuller et al, 2005), we focus on modifiable factors that may serve an important role in helping adolescents overcome exposure to stressful environments. To our knowledge, only three longitudinal studies have examined interactions with modifiable factors.…”
Section: Introductionmentioning
confidence: 99%